PEMANFAATAN SOSIAL MEDIA UNTUK DIGITAL MARKETING PADA SISWA JURUSAN TEKNIK DAN BISNIS SEPEDA MOTOR - Pramudhita Ferdiansyah; Muhammad Reza Yusril Syahputra (Muria Jurnal Layanan Masyarakat, 2023)
Currently the development of the world of education is increasing, especially in the fields of marketing and business. Where all majors or disciplines cannot be separated from marketing and business materials. This service focuses on vocational schools majoring in Motorcycle Engineering and Business. Where in the department there is already a curriculum on the motorcycle business. In improving the quality competence of SMK students majoring in Motorcycle Engineering and Business (TBSM) in developing business knowledge, it is necessary to introduce supporting aspects in the sale of goods or services, especially digital marketing. The training that will be carried out later is taking photos or pictures according to the composition of the photography so that the goods or products look more attractive, then simple editing of product photos. In addition, briefing on the use of social media to be used as a means of promotion or marketing of the selected products. The end result of this service is that students can get to know digital marketing and are able to manage and utilize social media to be used as a means of marketing or business. The material delivered is in accordance with the school curriculum majoring in Motorcycle Engineering and Business, so that the knowledge gained can be well integrated and can be used as a curriculum development for the School Engineering and Motorcycle Business major.